2020
DOI: 10.1161/jaha.119.015658
|View full text |Cite
|
Sign up to set email alerts
|

Rice Intake, Arsenic Exposure, and Subclinical Cardiovascular Disease Among US Adults in MESA

Abstract: Background Arsenic‐related cardiovascular effects at exposure levels below the US Environmental Protection Agency's standard of 10 μg/L are unclear. For these populations, food, especially rice, is a major source of exposure. We investigated associations of rice intake, a marker of arsenic exposure, with subclinical cardiovascular disease (CVD) markers in a multiethnic population. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Total urinary As and urinary DMA were found not to be associated with elevated serum PSA, even after accounting for urinary arsenobetaine which is typically used as a measure of overall seafood exposure [ 23 ]. The present study findings are consistent with a previous study that found no difference in total serum PSA between men exposed compared to men not exposed to high concentrations of As in drinking water [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total urinary As and urinary DMA were found not to be associated with elevated serum PSA, even after accounting for urinary arsenobetaine which is typically used as a measure of overall seafood exposure [ 23 ]. The present study findings are consistent with a previous study that found no difference in total serum PSA between men exposed compared to men not exposed to high concentrations of As in drinking water [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limit of detection (LOD) for total urinary As and urinary DMA was 0.83% and 12.1%, respectively [ 22 ]. Urinary arsenobetaine (LOD = 27.6%) was included in the sub-analysis to account for the influence of non-toxic seafood have on toxic As [ 23 ]. For total urinary As, urinary DMA, and urinary arsenobetaine, levels that were below LOD were divided by the square-root of two.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Podgorski and Berg estimated that 94 to 220 million people are potentially exposed to high concentrations of arsenic in groundwater worldwide [ 3 ]. Chronic arsenic exposure has been implicated in the development of various diseases, such as skin lesions, hypertension, cardiovascular disease, peripheral vascular disorders (e.g., Blackfoot disease), neuropathy, cancer, and arteriosclerosis [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Therefore, elucidating the mechanism of arsenic toxicity is important for the prevention and treatment of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that approximate 200 million people all over the world were affected by high level of As in drinking water, with the most serious situation in Bengal Delta 1,2 . In rice‐producing area, As could be accumulated in rice through irrigation with As‐contaminated water, and consumption of rice was reported to be a prominent intake pathway in these districts 3,4 . As was reported having deleterious effects on almost every system of human body and related to the occurrences of skin cancer, cardiovascular diseases, diabetes, adverse pregnancy outcomes, and peripheralneuropathy 5,6 …”
Section: Introductionmentioning
confidence: 99%